25 years at Knowledge-Based Systems: A bibliometric analysis - Cobo, Manuel Jesús; Martínez, Mª Ángeles; Fujita, Hamido; Herrera-Viedma, Enrique (Knowledge-Based Systems, 2018)
In commemoration of the Anniversary 25th of KnoSys we present a bibliometric analysis of the scientific content of the journal during the period 1991–2014. This analysis shows the conceptual evolution of the journal and some of its performance bibliometric indicators based on citations, as the evolution of its impact factor, its h-index, and its most cited authors/documents.
Keywords: bibliometrics; science mapping; citations; co-word analysis; h-index; JCR; Scopus